The Impact of Transformational Leaderhsip on Voice Behavior in Walubi Pematangsiantar - Chandra, Erbin; Sisca; Andy Wijaya; Lora Ekana Nainggolan; Onita Sari Sinaga (International Journal of Science, Technology & Management, 2022)
Transformational leadership is one type of leadership that is currently being discussed. This type of leadership is considered to be able to encourage voice behavior from members of an organization to produce useful opinions to create change for the better future for the organization. The purpose of this study was to investigate the influence of transformational leadership on member voice behavior in Walubi Pematangsiantar. The research population are all members (30 people) of Walubi Pematangsiantar. Data was collected through questionnaires, interviews, and documentation. Data analysis method used in this reasearch is simple regression analysis, correlation analysis, and hypothesis test (t test). The result showed that there was a positive effect between transformational leadership and voice behavior at Walubi at Pematangsiantar City. Hypothesis test result showed that transformational leadership had positive and significant effect to voice behavior. Suggestions for further research to increase the number of samples and organizations, and also increasing research variables so that new inputs that are more useful can be found, especially regarding the latest leadership issues. This study tries to make a Buddhist organization as an organization that is minority in Indonesia, and also not profit-oriented into an object of research that is rarely studied by scholars. The author also uses transformational leadership combined with voice habits as a research variable which is expected to be able to find a new finding that is effective in developing a non-profit organizations.